2016
DOI: 10.1016/j.jcf.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a national population carrier screening program on cystic fibrosis birth rate and age at diagnosis: Implications for newborn screening

Abstract: PCS markedly reduced CF birth rates with a shift towards milder mutations, but was often avoided for cultural reasons. As children regularly have significant disease at diagnosis, we suggest a balanced approach, utilizing both PCS and newborn screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…However, using the Israeli CF registry data it was suggested that the detection rate of the current Israeli preconception panel (Table ) is 70% (Stafler et al. ). Assuming that the patients included in our study represent the remaining 30% and that molecular diagnosis was reached in 78/152 (51.3%) cases, or 96 patients, some estimates can be made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, using the Israeli CF registry data it was suggested that the detection rate of the current Israeli preconception panel (Table ) is 70% (Stafler et al. ). Assuming that the patients included in our study represent the remaining 30% and that molecular diagnosis was reached in 78/152 (51.3%) cases, or 96 patients, some estimates can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the pan‐Israeli detection rate obtained by the Israeli screening program was calculated to be 70% (Stafler et al. ). This lack of homogeneity in the expected detection rates for the various Israeli subpopulations has been further complicated due to changing demographics secondary to immigration or intercommunity marriages, and the breaking of the link between kindred tribes and their traditional places of residence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest epidemiological review among new CF diagnosis in Israel, 36% were Arab and 64% Jewish, as compared to their proportion in the general population (20% and 75%, respectively). 30 There are differences in the ethnic distribution of different genotypes and unique mutations between the Arab and Jewish populations. 31,32 Interestingly, our study revealed that Arab ethnicity was correlated with a higher incidence of BOS and earlier onset of BOS compared to Jewish ethnicity in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…In the professional panel, program creators and Ministry of Health officials resented NBS for CF because, in their view, prenatal screening for this condition eliminates the need for mass screening and the right not to know genetic information, which is violated if a carrier is identified through molecular testing, as opposed to the "Dor Yeshorim" program which allows for matching couples before conception without disclosing their genetic information (program creator, personal communication, August 2016). Practitioners, on the other hand, have justified NBS for at least some CF mutations as an alternative for prenatal carrier screening, given the cultural barrier which prevents many pregnant women from performing prenatal screening for CF and the importance of early identification of the disease for prognosis [43]. Ultimately, NBS for CF was not included in the 2016 health basket (i.e., a procedure whose expenses are covered by the government).…”
Section: The Current State Of Nbs In Israelmentioning
confidence: 99%